Organized crime in Rio de Janeiro (Rivista di Studi e Ricerche sulla criminalità organizzata, 2016)
Since the nineties Brazil is fully included in the redefinition process of narcotrafficking’s routes and actors in South America. Nevertheless, international attention has been paid more to media events hosted in Brazil and to its economic and political situation than to the criminal one. This essay proposes an analysis of organized crime related to drug trafficking in Rio de Janeiro to fill that lack of attention. Following an introduction of Brazilian contest, the paper analyzes the evolution of criminal groups, focusing on their history, their organizational structure and on the interactions between tráfico, society and state institution.KEYWORDS: Brazil, narcotrafficking, Rio de Janeiro, favela, State, social control